Líquido amniótico: aspectos embriologicos, clínicos y ecográficos. Revision bibliográfica. - Chiliquinga Villacis, Sixto (2015)
The amniotic fluid is a component produced by the fetus. It acts mainly as protection for the fetus and provides a stable temperature, buffer against external trauma and allows the free movement of fluids necessary for normal lung development. This is a descriptive study for which information from different secondary sources, such as texts, magazines, website, was compiled by analyzing the contents and subtracting it relevant to the topic explained that explains the importance of the amniotic fluid by studying their origin, considerations clinics, ultrasound to assess the quality of life of the fetus. It is important for sonographers, given the diversity of methods described, unified metrics, considering the method of the four quadrants, described by Phelan, the most versatile, reproducible and constitutes the most widely used, in our country it is known and sought after as ILA. (Amniotic fluid index).